A Review of the Application of Steel Slag in CO2 Fixation. Issue 3 (11th March 2021) - Wang, Junya; Zhong, Mi; Wu, Pengfei; Wen, Shikun; Huang, Liang; Ning, Ping
Abstract: Steel slag is the main by‐product during the steel manufacturing process, with the characteristics of large output and low utilization rate. Since the high content of calcium oxide in steel slag, it is often used for CO2 capture. In this paper, progress on the development of steel slag for fixing CO2 is reviewed. This review is organized according to the carbonation type of steel slag, including direct carbonation and indirect carbonation. For direct carbonation, it is introduced from two parts: aqueous carbonation and gas‐solid carbonation. For indirect carbonation, it is summarized according to the extracting agent. The carbonation condition and capacity will be carefully discussed. Besides, the techno‐economic assessments of using steel slag for CO2 capture are discussed. This paper will provide an overview of the steel slag using for CO2 sequestration available and valuable suggestions for future study. Abstract : This review summarizes the progress of development of steel slag for fixing CO2 according to the carbonation type, including direct carbonation and indirect carbonation. The carbonation condition, capacity, and the techno‐economic assessments of using steel slag for CO2 capture are discussed. This review will provide an overview of the steel slag using for CO2 sequestration available and the valuable suggestions for future study.